1992
DOI: 10.1111/j.1600-0536.1992.tb05248.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skin irritancy of sodium lauryl sulphate: a comparative study between the replica method and visual evaluation

Abstract: For 20 years, using the replica method, we have evaluated the skin irritancy of about 10,000 commercial products which come into contact with the skin. In this method, test substances are usually applied on the flexor side of the upper arm for 24 h by semi-open patch test. Subsequently, skin replicas are taken and skin irritancy is evaluated microscopically. In the semi-open patch test, test substances are not completely occluded as in the closed patch test. Thus, this method is less invasive than the closed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…The results showed that statistically significant increases were present at grade 1þ versus grade 0, and showed deeper skin furrow in mild edema grade 1þ versus normal skin. This finding is similar with the result determined by Kawai et al [19] who used a replica to conduct the SLS patch test and reported that the most frequent change was a deepening of skin furrows. Moreover, all five SOT parameters showed statistically significant decreases at the higher visual grades, that is, on moving from visual grade 1þ to 3þ.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that statistically significant increases were present at grade 1þ versus grade 0, and showed deeper skin furrow in mild edema grade 1þ versus normal skin. This finding is similar with the result determined by Kawai et al [19] who used a replica to conduct the SLS patch test and reported that the most frequent change was a deepening of skin furrows. Moreover, all five SOT parameters showed statistically significant decreases at the higher visual grades, that is, on moving from visual grade 1þ to 3þ.…”
Section: Discussionsupporting
confidence: 91%
“…It was claimed that this method is more sensitive than the visual scoring system. However, these studies were comparative in nature and were based on simple visual observations of a replica rather than being reliant upon specific quantitative study [19]. Early studies on the objective and quantitative measurement of skin surface contours used a stylus profilometer [9].…”
Section: Discussionmentioning
confidence: 99%
“…(4) Since skin conditions were different in winter and summer due to sweating, dermal peeling force and TEWL were higher in winter while the amount of stripped corneocytes, hydration, and deepened skin furrows were higher in summer. (5) In winter, as the difference in dermal peeling force between the tapes was larger than in summer, the differences in the amount of stripped corneocytes and TEWL were also larger. Correlation coefficients : winter ; 0.910, summer ; 0.410 Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, irritation a¡ects the entire stratum corneum. When applying detergents for 24 h Kawai et al observed deepened furrows and membranous desquamation (32). Agner & Serup found 4 days after irritation with SLS (for 24 h, under occlusion) a rough pattern of non-parallel deep grooves (33).…”
Section: Discussionmentioning
confidence: 99%